Procedures and Tools Used by Teachers When Completing Functional Vision Assessments with Children with Visual Impairments. (September 2017) - Kaiser, Justin T.; Herzberg, Tina S.
Introduction: This study analyzed survey responses from 314 teachers of students with visual impairments regarding the tools and procedures used in completing functional vision assessments (FVAs). Methods: Teachers of students with visual impairments in the United States and Canada completed an online survey during spring 2016. Results: The majority of participants reported that they primarily assess pre-academic and academic students in kindergarten through 12th grade (K-12). More than 95% of all participants indicated that they assess near and distance visual acuity. Other commonly assessed skills and abilities were tracking ( n = 298; 95%), peripheral visual fields (n = 296; 94%), and color perception (n = 293; 93%). Approximately 50% of survey participants indicated that they use a screening tool in determining the need for an orientation and mobility (O&M) evaluation. Discussion: The procedures and tools used by participants in completing FVAs varied based on the specific student being assessed. There was also considerable variation in visual skills assessed, as well as in what was included in the assessment report by the participants. Based on comments from participants, it appears that there are complex factors that influence the decision-making process regarding possible referrals for an O&M evaluation or a clinical low vision evaluation. Implications for practitioners: Teachers should reflect on their own practices and procedures to determine whether they are including all pertinent information in their FVA reports, as well as explore whether they should assess additional visual skills in order to provide a rich description of how the student uses his or her vision throughout the day in a variety of environments.